Cross cultural comparison of constipation profiles at tertiary care centers between India and USA. Issue 8 (9th March 2018) - Singh, P.; Surana, R.; Soni, S.; Agnihotri, A.; Ahuja, V.; Makharia, G. K.; Staller, K.; Kuo, B.
Abstract: Background: Despite potential differences in patient perception of chronic constipation (CC) in geographically and culturally distinct regions, head‐to‐head studies comparing the clinical profile, constipation severity, impact on quality of life (QOL) and economic impact are lacking. Methods: We conducted a cross‐sectional cohort study of patients presenting with CC to tertiary care centers in the USA and India. Standardized instruments were used to assess constipation subtype, disease severity, disease‐specific QOL, somatization, and psychiatric comorbidities. We used multivariable linear regression to determine the predictors of QOL and number of healthcare visits. Key Results: Sixty‐six and 98 patients with CC were enrolled in the USA and India, respectively. Indian patients with CC had significantly more frequent bowel movements/week compared to their USA counterparts (Median 5 vs 3, P  < .0001). The proportion of patients with Bristol stool form scale type 1 and 2 was significantly higher in the USA compared to India (65.5% vs 48%, P  = .04). Higher depression score ( P  = .001), more severe constipation symptoms ( P  = .001) and site of the study being USA ( P  = .008) independently predicted worse QOL. Indian patients ( P  < .001) and worse QOL ( P  = .02) were independent predictors of number of healthcare visits in the last 12 months. Conclusions and Inferences: Indian patients with CC have more frequent and softer bowel movements compared to those in the USA suggesting significant differences in perception of CC in different geographic and cultural settings. QOL and economic impact related to constipation varies with geographic/cultural setting irrespective of other clinical and psychosomatic features. Abstract : Ours is the first study with head‐to‐head comparison of clinical profile, psychosomatic burden, constipation‐related symptoms severity, constipation specific quality of life and economic impact of chronic constipation between Indian and US patients presenting to tertiary care centres with chronic constipation. We found that Indian patients had significantly higher stool frequency and softer stool consistency (consistent with faster colonic transit) compared to US counterparts. We also showed that constipation‐related quality of life not only depends on symptom severity, psychiatric burden but also site of study (Site of study being USA was independent predictor of inferior quality of life). Nevertheless, after adjusting for other covariates, Indian patients had higher direct and indirect healthcare expenditures with increased work absenteeism due to constipation‐related symptoms and higher number of healthcare visits for constipation compared to their US counterparts.